Aplikasi Sandwich Plate System Berbahan Core Limbah Cangkang Kerang pada Geladak Kapal - Abdullah, Kharis; Zubaydi, Achmad; Budipriyanto, Agung (Wave: Jurnal Ilmiah Teknologi Maritim, 2018)
The development of technology in the field of materials and construction produces many innovations, one of them is sandwich plate system. Sandwich plate system is a material formed by two different materials into one layer. Sandwich plate system consists of face that from plate and core form composite. Clam shells are one of the waste materials that can be used as filler on the core. The composite material that use as a core is a mixture of clam shells powder as filler and resin as a matrix. The combination of clam shells powder and resin, produces strong composite materials. Sandwich plate system using core from clam shelsl powder and resin produce good strength. The material using 20% clam shells powder as filler of the resin weight has maximum stress 53.32 N/mm2 on the deck and 53.20 N/mm2 for 30% of filler by weight of the resin. The maximum stress value is still below the permission stress required by the class rule.